2022
DOI: 10.3390/polym14194181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethylene Glycol and Activated Carbon Macroparticles on Thermal Conductivity of Paraffin Wax for Thermal Storage Applications

Abstract: Low thermal conductivity is the major obstacle for the wide range utilization of phase change materials (PCMs), especially organic PCMs, for most practical applications in thermal engineering. This study investigates the potential of enhancing the charging and discharging rates of organic PCM (RT44HC) by introducing polyethylene glycol (PEG) and activated carbon macroparticles (ACMPs). Different concentrations of PEG and ACMPs ranging from 0.3 wt% to 2 wt% were tested separately. The optimized concentrations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The thermal conductivity of a material is directly proportional to its density [47]. Previous studies have reported similar trends for other particulate composites with different types of fillers, such as graphite [48], aluminum nitride [49], and aluminum [50]. However, the thermal conductivity values of particleboards with AC in this study are lower than those reported for other composites with similar filler contents [49,50].…”
Section: Thermal Properties Of Particleboardssupporting
confidence: 67%
“…The thermal conductivity of a material is directly proportional to its density [47]. Previous studies have reported similar trends for other particulate composites with different types of fillers, such as graphite [48], aluminum nitride [49], and aluminum [50]. However, the thermal conductivity values of particleboards with AC in this study are lower than those reported for other composites with similar filler contents [49,50].…”
Section: Thermal Properties Of Particleboardssupporting
confidence: 67%
“…Polyethylene glycol (PEG) has been used to form a stable suspension of activated carbon macroparticles (ACMP) in paraffin. 18 The effect of ACMP and PEG, as well as combinations thereof, on improving the thermal conductivity of PCM was studied. Various concentrations of components in the range from 0.3 to 2 wt % were used.…”
Section: Introductionmentioning
confidence: 99%